Soybean meal is necessary in diets for early-weaned (12 d of age) pigs - K Q Owen; Steven S Dritz; Michael D Tokach; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1993)
A total of 192 pigs (initially 8.0 lb and 12 d of age) was used to determine the optimal soybean meal level to be included in starter diets for the 12-d-old weaned pig. The trial was a 28 d growth assay. Pigs were allotted by weight to six replicates of four treatments with six or 10 pigs per pen. From d 0 to 14 postweaning, pigs were fed a common diet or experimental diets containing 5, 10, and 15% soybean meal. These high nutrient dense diets were formulated to contain 1.7% lysine. All pigs were fed a common transition diet from d 14 to 21 postweaning formulated to contain 1.4% lysine and a common phase II diet from d 21 to 28 postweaning formulated to contain 1.25% lysine. Linear improvements in average daily gain (ADG) and average daily feed intake (ADFI) were observed in the d 0 to 14 postweaning period as soybean meal increased from 0 to 15% of the diet. No differences in growth performance were observed when pigs were fed the common transition and phase II diets from d 14 to 21 postweaning and d 21 to 28 postweaning, respectively. Pig weights on d 14, 21, and 28 postweaning improved linearly. Thus, the improvements in ADG and ADFI for the cumulative (d 0 to 28 postweaning) period were a result of the performance in the d 0 to 14 postweaning period. The advantage in pig weight on d 14 postweaning was maintained through d 28 postweaning. In conclusion, soybean meal can replace skim milk and be included at a level between 10 and 15% in the diet of pigs weaned at 12 d of age.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Starter; Soybean meal; Skim milk